Scale invariant fractal textures of serum albumin and Na-DNA films from solutions with metal halides - Glibitskiy, G. M. (Biophysical Bulletin)
Fractal texture features of the albumin and Na-DNA films with fluoride, chloride and bromide of sodium analyzed. The films were obtained from bovine serum albumin and human serum albumin ("Sigma-Aldrich") solutions at a concentration of 0.5 mg/ml in the presence of sodium salts at a concentration of 20 mM, and from the solution of Na-DNA ("Serva") with a concentration of 0.25 mg/ml in the presence of a metal chloride at a concentration of 10 mM. The geometrical parameters of textures differ depending on location on the surface of the cuvette and the composition of the ions in solution. Increased density of scale invariant fractal textures in the central part of the cuvette may be explained by the redistribution of salts and biopolymers on the surface of the cuvette during the solution drying. Periodic structures with characteristic repetition period of L2≈ 4÷6 microns are present in the individual structural elements. The scale invariant fractal textures are formed on the surface of films with sodium, potassium and rubidium chlorides.